Produktivitas Kerja Pegawai Ditinjau dari Integritas, Kompetensi dan Pengalaman Kerja - Suharno; Istiatin; Fithri Setya Marwati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study uses a quantitative approach with a quantitative descriptive method to determine the magnitude and significance of the influence and significance between the variables of integrity, competence and work experience on employee work productivity. This research was conducted at the Surakarta City Bapenda Office which is located at Jl. Jendral Sudirman No. 2, Kampung Baru Village Hall Complex, Surakarta 57111. The research time was carried out for 6 (six) months. The population in this study is 55 TKPK employees who work at the Surakarta City Bapenda. The sample taken in this study was 55 respondents.  The sampling technique used in this study is the census technique. The census method is a sampling technique when all members of the population are used as samples. The variables used in this study consist of 2 variables, namely independent variables and dependent variables. The independent variables consist of integrity, competence and work experience and the dependent variable is employee work productivity. Multiple linear regression tests are used in this study to test the research data. Integrity, Competence, and Work Experience have a positive and significant effect on the work productivity of employees of the Surakarta City Bapenda Office.  Based on the calculation results, an adjusted R square value of 0.686 was obtained. This means that the variables of integrity, competence and work experience contribute to employee work productivity by 68.6% while the remaining 31.4% is explained by other variables that were not proposed in the study